ماهية كتب النوازل ومدى ارتباطها بحياة الناس (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف البحث إلى تبيين كيفية معالجة القضايا والأسس والقواعد والضوابط التي يجب اعتمادها للوصول إلى الحكم الشرعي الصحيح في كتب النوازل, وإبراز مقدرة الفقه الإسلامي وفاعليته في تقديم الحلول المناسبة, وذلك من خلال المسائل التالية: • التعرف على النازلة• مراحل كتب النوازل• خصائص كتب النوازل• أشهر كتب النوازل وانطلاقاً من معالجة هذه القضايا يتم توضيح ماهية كتب النوازل ومدى ارتباطها بالناس. This research aims at spotting the light on the way to deal with the issues, cases and the rules that should be relied on to reach the right legitimate judgement in Nawazel Books. It also shows the efficiency of Islamic doctrine in presenting suitable solutions. This will be done through the following steps: • Identifying and introducing Nazelah• The stages of Nawazel Books. • The characteristics of Nawazel Books.• The most famous Nawazel Books. The nature of Nawazel Books and their relation to people will be shown clearly through dealing with the aforementioned issues.